Fostering Undergraduate Student’s Critical Reading Skill through Multimodal Text - Nurjanah, Kokom (LPPM STKIP Kusuma Negara, 2024)
This present study investigates the development of under graduate students’ critical reading skills through multimodal text. Multimodal text is a text that contains semiotic mode which covers gesture, visual image, document, layout, music, architectural design, etc. The design of this study classroom action research (CAR) since the study aims to improves students’ critical reading skill and solve several problems arouse in teaching and learning. The participants of this study are twenty-four undergraduate students studying at English education study program in STKIP Kusuma Negara. Based on the characteristics of CAR, it is done repeatedly until those problems can be overcome. Four instruments covering critical reading test, classroom observations, questionnaire, and interview were conducted as data collections of this study. The results of this study indicates that the students’ critical reading skills improved significantly after using multimodal text as media in teaching and learning process. This study is expected to give an insight and contribution for English pedagogy.